Acquisition and maintenance of motor memory through specific motor practice over the long term as revealed by stretch reflex responses in older ballet dancers. Issue 2 (20th January 2020) - Kim, GeeHee; Ogawa, Tetsuya; Sekiguchi, Hirofumi; Nakazawa, Kimitaka
Abstract: The present study addressed whether motor memory acquired earlier in life through specific training can be maintained through later life with further training. To this end, the present study focused on the training effect of a specific ballet practice and investigated the spinally mediated stretch reflex responses of the soleus muscle in ballet dancers of upper‐middle to old age (60.6 ± 5.4 years old) with experience levels of 28.4 ± 7.4 years ("older ballet" group). Comparisons were conducted with a group of young ballet dancers ("young ballet" group) and groups of both young and older individuals without weekly participation in physical activities ("young sedentary" and "older sedentary" groups). The results revealed natural age‐dependent changes, with reflex responses being larger in older sedentary than in young sedentary individuals. A training‐induced effect was also observed, with responses being smaller in ballet dancers than in sedentary groups of the same age. Furthermore, the responses were surprisingly smaller in the older ballet dancers than in the young sedentary group, at an equivalent level to that of the young ballet dancers. The influence of training, therefore, overcame the natural age‐dependent changes. On the other hand, the onset latencies of the responses showed a solely age‐dependent trend. Taken together, the present is the first to demonstrate that the motor memories in the spinal cord acquired through specific ballet training earlier in life can be maintained and carried forward in later life through further weekly participation in the same training. Abstract : With the knowledge that human motor system undergoes functional changes after participation in specific motor training, the present study first demonstrated that the motor memories in the spinal cord acquired through participation in specific ballet training earlier in life can be maintained and carried forward in later life through further weekly participation in the training.